Measurement of the B0-B̄0 oscillation frequency δmd with the decays B0→D-π+ and B0→J/ψK*0 - Aaij, R; Abellan Beteta, C; Adametz, A; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; et al. (2013)
The B0-B̄0 oscillation frequency δmd is measured by the LHCb experiment using a dataset corresponding to an integrated luminosity of 1.0fb-1 of proton-proton collisions at √s=7TeV, and is found to be δmd=0.5156±0.0051(stat.)±0.0033(syst.)ps-1. The measurement is based on results from analyses of the decays B0→D-π+ (D-→K+π-π-) and B0→J/ψK*0 (J/ψ→μ+μ-, K*0→K+π-) and their charge conjugated modes. © 2013 CERN.